The framework of improving on-site materials tracking for inventory management process in construction projects - Liwan, Siti Radziah (2015)
Inventory management is important especially in construction projects because materials and components constitute 50-60% of the total project cost. While inventory management has increased concerned among various parties within the project, materials tracking for inventory management also act the same way. Material tracking could provide timely information on materials availability and enables realtime on-site measurement of the project performance which is important for inventory management. However, material tracking practices in construction projects has been using manual method and it has many drawbacks. Although the application of advanced technology is needed as it has ability to assist materials tracking, however; there is still lack of materials tracking framework for inventory management process in construction projects. Therefore, the research aims to fill in this gap by developing an on-site material tracking framework for improving inventory management processes in Malaysian construction projects. In this research, potential implementation of RFID technology for materials tracking and the existing material tracking practices in construction projects were identified. Literature review and case studies approach were conducted to obtain data of the research. Ten case studies was undertaken to investigate inventory management process and material tracking practices in Malaysia construction projects. The data analysis involves both within case analysis and cross-case analysis. The findings conclude by developing an on-site material tracking framework for inventory management process which consists of seven components namely; manufacturing, materials delivery, materials arrival, materials storage, materials use, on-site control centre and report generation. The framework would be beneficial for contractors having intention to adopt RFID technology to assist and facilitate materials tracking particularly at the site storage area.